Exploring opportunities and risks of artificial intelligence research for islamic ethical guidelines - Aliff, Nawi; Nor Yazi, Khamis; Mohd Faiz, Yaakob; Mohd Al Adib, Samuri; Zakaria, Gamal Abdul Nasir (University of Malaya, 2023)
Artificial intelligence (AI) technology is expanding exponentially. AI has continuously transformed the human lifestyle from chatbots, driverless vehicles, robots, autonomous weapons constructions, etc. The transformation has driven the development of guidelines from various fields to govern AI research and development but is limited from Islamic perspectives. Hence, this study aims to fill the gap by reviewing contemporary perspectives on AI opportunities and risks. A qualitative exploration using content design analysis on related literature was conducted to ascertain the extent of AI utilisations by applying used, overused, or misused. The findings were coded in juxtapositions that led to the discussion on the need for an Islamic frame of reference in ethically guiding AI-related research. Maqasid al-Shari‘ah is recommended as the parameter and to be integrated with other disciplines to tackle the wide-ranging ethical issues in AI to protect human rights and interests, particularly in the global Muslim community. The absence calls for developing a credible and robust framework to serve as an Islamic ethical guideline for AI research.